AB1079 The double contour sign is a consistent finding in MTP joints in gout patients. Results from an ultrasound pilot study in daily clinical practice. (23rd January 2014) - Slot, O.; Terslev, L.
Abstract : Background: Ultrasound (US) is more sensitive than Magnetic Resonance Imaging, Computed Tomography and X-ray for detecting changes in gout. The findings in gout include the double contour sign (DC), tophi, concentric synovial thickening and erosions 1, 2 . The DC sign is a hyperechoic delineation of the cartilage, caused by urate crystal deposits on the surface of the cartilage. DC is easily separated from the normal "cartilage sign" which is only seen when the insonation angle is 90°. As the DC sign is a characteristic, easy recognizable and specific feature 3 even in joints without previous gout attacks 1 it might become "the sign to look for" when evaluating patients with a suspected diagnosis of gout in the daily clinical practice. Objectives: Systematically to evaluate the frequency of the DC sign in joints of the lower extremity in patients with gout at the time of diagnosis in daily clinical practise Methods: During a 3 months period all consecutive patients with newly diagnosed gout (clinical diagnosed confirmed by detection of negatively birefringent crystals by microscopy of joint aspirate) were examined with US of the metatarsophalangeal (MTP) joints and the knee joints bilaterally. The MTP joints were evaluated longitudinally dorsally with and without flexion and the knees were evaluated transversally in a flexed position. All examinations were performed in B-mode with a Logiq 9 (GE Medical, Milwaukee, WI, USA) using a 14MHz centre frequency linear array transducer. The presence of DC sign in any of the investigated joints was registered and subsequently confirmed by consensus by both authors. Results: 15 patients (13 males, 2 females, age 71(35-87) years, median duration of symtoms 48(2-280) months, p-urate 0.55(0.41-0.86) mmol/l (medians(range))) were enrolled. The DC sign in MTP joints was found in 15/15 patient, while the DC sign in the knees was found in 6/14 patients. Conclusions: The US DC sign in MTP joints was found in all the patients in this observational pilot study of patients with newly diagnosed and microscopy proven gout. DC in the knee joints were more seldom occurring. These findings indicate that the DC sign of the MTP joints may become a useful screening marker of the disease. Further studies are needed to evaluate the sensitivity and specificity of DC sign in gout patients. As the DC sign may also be found in patients with asymptomatic hyperuricemiae 4 the prognostic value for developing gout attacks also remains to be established. References: Wright SA et al. High resolution ultrasonography of the first metatarsal phalangeal joint in gout: A controlled study. Ann Rheum Dis 2007;66:859-64. Thiele RG. Role of ultrasound and other advanced imaging in the diagnosis and management of gout. Curr Rheumatol Rep 2011;13:146-53. Filippucci E et al. Hyaline cartilage involvement in patients with gout and calcium pyrophosphate deposition disease. An ultrasound study. Osteoarthritis Cartilage. 2009;17:178-81. Pineda C et al. Joint and tendon subclinical involvement suggestive of gouty arthritis in asymptomatic hyperurecemia: an ultrasound controlled study. Arthritis Res Ther 2011;13:R4. Disclosure of Interest: None Declared